A Positive School Climate Based on the Reinforcement of Islamic Values - Maputra, Yantri; Susanti, Meria; Afrinaldi, Afrinaldi; Dwi Maputra, Supardi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This research aims to examine a positive school climate or environment through the reinforcement of religious values. This study employs a qualitative research method with a case study approach. Data collection was conducted through individual and group interviews and observations at four high schools in Sijunjung Regency. Group interviews were conducted with a total of 20 teachers and were followed by in-depth interviews with four teachers. Data analysis was performed using Nvivo software. The results indicate that a positive school climate can be fostered through the reinforcement of religious values. The religious values identified as a result of this study include the habitual behaviors of greeting others, shaking hands, saying hello, praying before studying, performing congregational prayers, reciting Asmaul Husna, reading the Quran for 15 minutes before studying, praying before studying and giving to charity. It can be concluded that the habituation of religious values can serve as an effort to create a positive school climate that will have beneficial effects on both the school culture and the psychological well-being of students.